Effect of osteopathy on tennis players with shoulder pain - Janossa, M. (2002)
This pilot study about the effect of osteopathy on tennis players with shoulder pain was conducted, involving 30 active, semi-professional tennis players with chronic shoulder pain that caused difficulties and ineffectiveness in serving. The patients were divided into three groups: those receiving osteopathic treatment combined with relevant strengthening and stretching exercises, those receiving only exercise advice without osteopathic treatment, and those receiving no advice and no treatment. In all cases, comparative muscle tests with Dynamic Myograph (BCNO] were carried out on the deltoid muscles before and after the assessment and treatment period. The treatment course was four sessions at weekly intervals. All patients in the study suffered from repetitive rotator cuff tendonitis, deltoid muscle weakness, muscular imbalance between the external and internal rotators of the dominant shoulder by the weakness of external rotators, combined with structural changes in the cervical and thoracic spinal area. The deltoid muscle strength improvement occurred only after the treatment of the relevant spinal segments. Stretching exercises must be gentle in the first two weeks, because the overworking effect can influence the already vulnerable muscles, such as the external rotators. Age and lifestyle influence the outcome. The benefits of osteopathy are to reduce prescription of non-steroid anti-inflammatory drugs, reduce the illness behaviour, avoid unnecessary investigations and achieve early relief. Treatment always starts on the day of the first consultation. The tennis players could continue their sport activities using a modified, under-arm serving technique and came back to full strength and overhead serving in a short period of time. Local steroid injections, one of the common non-surgical treatments for chronic tendon lesions, are a cause of concern because of their potential adverse effects on the tendons. The literature contains very many reports of complications following intra- or peri-articular infiltration with steroids.